If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -6 = 10 + 6x Reorder the terms: -6 + 10x = 10 + 6x Solving -6 + 10x = 10 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -6 + 10x + -6x = 10 + 6x + -6x Combine like terms: 10x + -6x = 4x -6 + 4x = 10 + 6x + -6x Combine like terms: 6x + -6x = 0 -6 + 4x = 10 + 0 -6 + 4x = 10 Add '6' to each side of the equation. -6 + 6 + 4x = 10 + 6 Combine like terms: -6 + 6 = 0 0 + 4x = 10 + 6 4x = 10 + 6 Combine like terms: 10 + 6 = 16 4x = 16 Divide each side by '4'. x = 4 Simplifying x = 4
| 0.16(12)+0.04x=0.08(24+x) | | 3y+2-2y-5=-2x-2 | | (2x+1)+(4-3x)=10 | | 7z-10-z+4=0 | | x+2*x+2*x+2*x+2+11=49 | | x+1/3-x+2/4=x+1 | | 7x+5-2x+1=4x+8 | | 9x^4-16x^2=0 | | 6-4v+4=v+5 | | 0=2(2x^3+3x^2+7x-5) | | 14x+140=147+13 | | 3t+21= | | x^2+19x-216=0 | | 2x+2(x-20)=212 | | n^4-9n^2=0 | | 3(0.3-4.5v)=-32.1-7.5v | | 3x^2-36=(3x-2)(x-2) | | x(5x+10)=0 | | x=-1+2y | | 2(m-3)=6 | | 5x-9x+12=-2x+6 | | 0=4x^2+11x-3 | | x^2-5x-8=-6x-2 | | 4(c-2)=7(c+1) | | 50n^3-2n=0 | | 7-6x=31 | | x^2+x-13=7 | | 9*7+8*3= | | 2(m-3)=-12 | | 45x(4+3)=1000 | | (6a-2)(5a-4)= | | w(9+-1w^2)= |